Profit in American Economic Theory - Hopkins, William S. (Review of Economic Studies, 1933)
Journal Article Profit in American Economic Theory Get access William S. Hopkins William S. Hopkins Stanford University, California, U.S.A. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 1, Issue 1, October 1933, Pages 60–66, https://doi.org/10.2307/2967438 Published: 01 October 1933